Differential immunoglobulin and complement levels in leprosy prior to development of reversal reaction and erythema nodosum leprosum. - Francianne M Amorim; Maurício L Nobre; Larissa S Nascimento; Alesson M Miranda; Glória R G Monteiro; Francisco P Freire-Neto; Maria do Carmo Palmeira Queiroz; José W Queiroz; Malcolm S Duthie; Marcos R Costa; Steven G Reed; Warren D Johnson; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Leprosy is a treatable infectious disease caused by Mycobacterium leprae. However, there is additional morbidity from leprosy-associated pathologic immune reactions, reversal reaction (RR) and erythema nodosum leprosum (ENL), which occur in 1 in 3 people with leprosy, even with effective treatment of M. leprae. There is currently no predictive marker in use to indicate which people with leprosy will develop these debilitating immune reactions. Our peripheral blood mononuclear cell (PBMC) transcriptome analysis revealed that activation of the classical complement pathway is common to both RR and ENL. Additionally, differential expression of immunoglobulin receptors and B cell receptors during RR and ENL support a role for the antibody-mediated immune response during both RR and ENL. In this study, we investigated B-cell immunophenotypes, total and M. leprae-specific antibodies, and complement levels in leprosy patients with and without RR or ENL. The objective was to determine the role of these immune mediators in pathogenesis and assess their potential as biomarkers of risk for immune reactions in people with leprosy. METHODOLOGY/FINDINGS:We followed newly diagnosed leprosy cases (n = 96) for two years for development of RR or ENL. They were compared with active RR (n = 35), active ENL (n = 29), and healthy household contacts (n = 14). People with leprosy who subsequently developed ENL had increased IgM, IgG1, and C3d-associated immune complexes with decreased complement 4 (C4) at leprosy diagnosis. People who developed RR also had decreased C4 at leprosy diagnosis. Additionally, elevated anti-M. leprae antibody levels were associated with subsequent RR or ENL. CONCLUSIONS:Differential co-receptor expression and immunoglobulin levels before and during immune reactions intimate a central role for humoral immunity in RR and ENL. Decreased C4 and elevated anti-M. leprae antibodies in people with new diagnosis of leprosy may be risk factors for subsequent development of leprosy immune reactions.